Microplastics Abundance and Characteristics in Mytilus spp. from Southwest Western Australia Urban Estuaries - Saraswati, Ni Luh Gede Rai Ayu; Paterson, Harriet; Hovey, Renae (International Journal of Environment and Geosciences, 2022)
As global plastic production continuously increases, plastic waste is no doubt becoming an emerging threat to aquatic ecosystems. This condition has directly linked to the abundance of microplastics in the aquatic system, especially in the semi-enclosed system of estuary. This study aims to investigate the microplastics abundance and characteristics in sedentary filter feeder of Mytilus spp. inhabited urban estuaries of southwest Western Australia. Microplastics were detected in 69% of total individual sampled. The mean of microplastics was 1.31±1.26 items per invidual and 0.27±0.45 Items per mussels wet weight (gww). The most common microplastics types from all samples was films (51%), then followed by fibers (43%). Our results highlight that microplastics contamination is widespread across the Western Australia estuaries and has contaminated the sedentary organisms lived in the estuary, including Mytilus spp. This study was a pilot study and is considered to be the first study in Western Australia among similar studies on microplastics in mussels. A further study in developing standard methods and expanding the study area and sample size is important to be conducted. This will give more confirmation on using mussels ( Mytilus spp.) for global microplastics biomonitoring. Keywords: Microplastics; Mussel;  Mytilus spp.; Urban Estuary; Southwest Western Australia